Implementasi OWASP Mobile Security Testing Guide (MSTG) Untuk Pengujian Keamanan Pada Aplikasi Berbasis Android - Luqman Hakim Yumnun; Ari Kusyanti; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
OWASP Mobile Security Testing Guide (MSTG) is a method that can be used for security testing on mobile device applications both based on iOS and Android operating systems. Security testing is needed to minimize vulnerabilities in an application. However, there is currently no security testing application that applies OWASP MSTG, so this research will create a security testing system that applies OWASP MSTG. In the requirement analysis process there are 11 functional requirements while the design phase will make the system design, interface design, and algorithm design. This system is implemented on a web-based using CodeIgniter framework. On system testing, the system is tested by functional testing and validation testing by comparing the results of the system that has been made with existing security testing applications. Based on the system testing, the security testing system OWASP MSTG has been running and accordance with the system design stage.